2016
DOI: 10.1039/c6sc02555b
|View full text |Cite
|
Sign up to set email alerts
|

Templated dewetting: designing entirely self-organized platforms for photocatalysis

Abstract: Noble metal dewetting on self-organized TiO2 nanotubes – nanoscopic design of photocatalysts towards green H2 generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 154 publications
0
99
0
Order By: Relevance
“…TiO 2 NTs have attracted considerable interest in photocatalysis and photo‐electrochemistry in the last decades due to their reliable and versatile fabrication method, high surface area and one‐dimensional (1D) morphology; namely the latter can provide attractive charge transport properties . Moreover, in the context of the present work, these highly‐ordered TiO 2 nanotube layers can be used as a defined, corrugated photo‐active surface to host the formation of the nanoporous Pt co‐catalyst by a dewetting‐alloying‐dealloying approach …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 NTs have attracted considerable interest in photocatalysis and photo‐electrochemistry in the last decades due to their reliable and versatile fabrication method, high surface area and one‐dimensional (1D) morphology; namely the latter can provide attractive charge transport properties . Moreover, in the context of the present work, these highly‐ordered TiO 2 nanotube layers can be used as a defined, corrugated photo‐active surface to host the formation of the nanoporous Pt co‐catalyst by a dewetting‐alloying‐dealloying approach …”
Section: Resultsmentioning
confidence: 99%
“…[39] Moreover, in the context of the present work, these highly-ordered TiO 2 nanotube layers can be used as a defined, corrugated photo-active surface to host the formation of the nanoporous Pt co-catalyst by a dewetting-alloying-dealloying approach. [34,35,40] The TiO 2 NTs were grown by self-organizing electro-chemical anodization of a Ti metal foil in a hot HF/o-H 3 PO 4 electrolyte. [41] The SEM image in Figure 1 a shows the morphology of as-prepared structures.…”
Section: Resultsmentioning
confidence: 99%
“…However,a s-formed tube membranes are amorphous and in order to form photocatalytically active anatase TiO 2 membranes, the Pt/TiO 2 structures are annealed in air at 500 8Cf or 1h.O wing to the thermal treatment, and as shown in Figure 1c-f and in Figure S1, the Pt depositeda tt he oxide surfacef orms particles andi slands.T his result can be ascribed to solid-state dewetting, that is, the Pt films (when < than ac riticalt hickness) tend to agglomerate into particles and expose the oxide (substrate) surface as ar esult of the minimization of the free surface energy of the metal film, of the oxide and of the metal-oxide interface. [54] Particularly,t he morphology of the substrate (in this case TiO 2 tube top and bottom) and the amount of sputtered metal largely affect the size and distributiono ft he deposited Pt decorations, [55] as showni nF igureS2. Af irst general finding that is well in line with theory on dewetting is that the thicker the metal film, the larger the dewetted particles and the broader their size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be ascribed to templated dewetting:t he periodic geometry of the tube bottom provides ad efined pathway for metal film rupture and consequento rdered agglomeration of the Pt film into NPs. [30,54,55] Figure 2shows various cross-sectional SEM images of Pt-decorated NT membranes.T he images are taken at the very top and bottomo ft he tube layers. The penetration depth of the Pt NPsd epends on the structure of the tube substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the observed photocatalytic improvement seems to be ascribed to an increase of the Au decoration density on the NTs. [18,28] Nevertheless, in an attempt to further increase the Au NP density, we found that the structures grown from homogeneous alloys with a Au content of 2 at.% (H2) show a significantly lower rH2 (2.1 µL h -1 cm -2 ). The reason for this is that these substrates, owing to their relatively high Au content, do not grow ordered NTs but only undefined Au-TiO2 porous structuressee Fig.…”
mentioning
confidence: 92%